Parents' expectations in their child's private music lessons / Nadira Zulkifli - Zulkifli, Nadira (2013)
Parents have different educational believes and expectations when it comes to their children's education. The objective of this study is to identify the parents' reasons for enrolling their children in private music lessons, and their expectations and valuing towards private music lessons. The expectancy-value theory of motivation by Eccles et al. was used as the basis for investigation. Data was collected using a survey questionnaire from among 167 parents who enrolled their children in private music classes located in several areas of the Klang valley. Results show that the main parents' reason in enrolling their child in private music lessons is to provide their child with the enjoyment of playing a musical instrument and they were expecting that their child would have a balanced education when they enroll their child in private music lesson, in addition, between the three motivational constructs, parents in this study valued their child's music learning as usefulness than interest and importance.